Políticas de defesa e segurança colombiana de Álvaro Uribe e Juan Manuel Santos (2002 - 2012): análise sobre mudanças e continuidades para solução do conflito armado - Abumansur, Rochele Karina Costa de Moraes (2013)
This research has as its central objective comparative analysis of defense and security plans adopted by the Colombian government of Alvaro Uribe and Juan Manuel Santos, as well as its political and security agendas. This study considers the common defense and security as State Policy which is part of the common foreign to consider as the main threat to state security to Colombian guerilla activity, production of drug trafficking and human rights abuses suffered by the population. The time frame relevant to the purposes of the research extends the Alvaro Uribe government (2002 - 2010) to half of the first term of the government of Juan Manuel Santos (2010 - 2012), in as much as in the previous period only serves to support historic for understanding of recent events. The main conclusion of this study focuses on detecting differences and / or similarities between the security plans of both governments to resolve the matter then whether there is progress or setbacks in the solution of the Colombian conflict and the search for peace in that country.